The role of strength on punch impact force in boxing - Beattie, K.; Ruddock, A. D. (The Journal of Strength and Conditioning Research, 2022)
The ability to punch with a high impact force is beneficial to boxers as there is an increased likelihood of success. Punch impact force differentiates between performance level, weight class, gender, and punch type in competitive boxers. Although technique is likely to play a major role in punch impact force, the capabilities of the neuromuscular system may also be a limiting factor. This review examines the role of strength on punch impact force in amateur and professional boxers. The maximal strength qualities of the lower body, as well as explosive strength qualities of both the upper and lower body, are largely associated with punch impact force in elite amateur boxers. Specifically, elite amateur boxers who punch with "high" impact forces have greater levels of lower-body maximal strength and explosive strength when compared with elite amateurs who punch with "low" impact forces. However, the maximal strength capabilities of the upper body are not associated with punch impact force and does not differentiate between elite boxers who punch with "high" and "low" impact forces. Therefore, based off the present evidence, this review recommends that for boxers who aim to develop their punch impact force, it may be advantageous to emphasize both maximal and explosive strength development of the legs, with only an explosive strength focus in the upper body. However, it is important to highlight that, to date, there are a lack of experimental studies in both elite amateur and professional boxing. Furthermore, there is a dearth of research in female boxing. Future experimental studies are needed to infer causality regarding the role that strength training has on punch impact force in both elite amateur and professional boxers.